Does Modernizing Union Administrative Practices Promote or Hinder Union Revitalization? A Comparative Study of US, UK and Australian Unions. (1st April 2020) - Clark, Paul F.; Bamber, Greg J.; Whitehead, Paul V.; Gray, Lois S.; Cockfield, Sandra; Gilbert, Kay
Abstract: Can a union be both democratic and administratively efficient, or are these goals always at odds? Building on the Webbs' focus on this critical question, this article analyses and compares the changing administrative policies and practices of US, UK and Australian trade unions over a 25‐year period. We conducted surveys of unions in all three countries to gather information on union policies and practices involving the unions' human resources, hiring, budgeting and strategic planning. Using these novel longitudinal data, we contribute to industrial relations scholarship by showing that unions have increasingly adopted formal, systematic practices in these areas. The article is grounded in theory and also has practical relevance given the important implications that our findings may have for the revitalization of unions in the three countries and beyond.